GEDEF: sistema de gerenciamento de defeitos em ambiente geral. - ALMEIDA, Breno Xavier de; FORTE, Leticia da Silva; ROCHA, Samara de Oliveira; PEREIRA, Stefani dos Santos (138, 2019)
O objetivo principal desse trabalho é apresentar o desenvolvimento de um sistema de manutenção em ambientes diferenciados. Tal sistema tem por finalidade cadastrar problemas identificados em equipamentos diversos ou em locais específicos de empresas, escolas, fábricas e outros, elencando as eventuais avarias. O sistema deve facilitar o gerenciamento dos defeitos tornando os processos mais rápidos e eficazes, trazendo benefícios para funcionários, gerentes, alunos ou outras pessoas que utilizam aquele local. O sistema será implementado visando atender todas as necessidades do ambiente, cadeiras, lixeiras, computadores, janelas, etc.

The main objective of this task is to present the development of a maintenance system in different environments. Such a system aims to register problems identified in various equipment or in specified locations of companies, schools, factories or others, by the issuance of reports listing possible malfunctions. The system must facilitate the defect management making the processes fasters and effective, bringing benefits for the employees, managers, students or others that use the site. The system will be implemented to meet all the needs of the environment, as notes are usually made on sheets or notebooks, or even not recorded anything that (which) ends up not repairing the problem. The system will have a registration screen where the defects of chairs, dumpsters, computers, windows etc.
GEDEF: general environment defect management system.
Keywords: Manutenção preditiva (gerenciamento); Equipamentos; Informática; Informação e Comunicação